Fractionation and Identification of Phytochemicals and Antioxidant Activity of Wild Grape (Ampelocissus martinii Planch.) Seed Extracts - Siripipatthana, P.; Srihanam, P. (Asian Journal of Chemistry, 2020)
A methanolic extract of wild grape (Ampelocissus martinii Planch.) seed at green (immature) growth stage was partially purified using silica gel chromatography, before the investigation of total phytochemicals and antioxidant activity of sub-fractions. The ethyl acetate/methanol at 3:1 (v/v) fraction had higher phytochemicals and antioxidant activities than others. The gallic acid, myricetin, and resveratrol were dominant phenolic substances in this fraction. However, ethyl acetate sub-fraction found the highest content of epicatechin and catechin. A correlation test indicated a strong positive trend between antioxidant activity and all tested of the phytochemical contents. The obtained results indicated that the wild grape seed contains compounds with excellent antioxidation capacity. That might be applied as an active ingredient in health-supporting products or active ingredients in cosmetics.